Evaluating GNSS integrity augmentation techniques for UAS sense-and-avoid - Sabatini, Roberto; Moore, Terry; Hill, Chris; Ramasamy, Subramanian (2015)
Global Navigation Satellite Systems (GNSS) far exceed the navigation accuracies provided by other state-of-the-art sensors for aerospace applications. This can support the development of low-cost and high performance navigation and guidance architectures for Unmanned Aircraft Systems (UAS) and, in conjunction with suitable data link technologies, the provision of Automated Dependent Surveillance (ADS) functionalities for cooperative Sense-and-Avoid (SAA). In non-cooperative SAA, the adoption of GNSS can also provide the key positioning and, in some cases, attitude data (using multiple antennas) required for automated collision avoidance. A key limitation of GNSS for both cooperative (ADS) and non-cooperative applications is represented by the achievable levels of integrity. Therefore, an Avionics Based Integrity Augmentation (ABIA) solution is proposed to support the development of an integrity-augmented SAA architecture suitable for both cooperative and non-cooperative scenarios. The performance of this Integrity-Augmented SAA (IAS) architecture was evaluated in representative simulation case studies. Additionally, the ABIA performances in terms of False Alarm Rate (FAR) and Detection Probability (DP) were assessed and compared with Space-Based and Ground-Based Augmentation Systems (SBAS/GBAS). Simulation results show that the proposed IAS architecture is capable of performing high-integrity conflict detection and resolution when GNSS is used as the primary source of navigation data and there is a synergy with SBAS/GBAS in providing suitable (predictive and reactive) integrity flags in all flight phases. Therefore, the integration of ABIA with SBAS/GBAS is a clear opportunity for future research towards the development of a Space-Ground-Avionics Augmentation Network (SGAAN) for UAS SAA and other safety-critical aviation applications.